The Epistimology of Science Immanuel Kant's Perspective: Epistemologi Sains Perspektif Immanuel Kant - Mannan, Abd; Hunain, Ishaq; Ramadhana, Maghfiroh (Jurnal Filsafat Indonesia, 2025)
Humans as creatures endowed with the privilege of reason cannot be separated from the thinking process. Thinking requires knowledge or something that is known in order to gain other knowledge in the process with certainty (true). The focus of this research is how the style of Immanuel Kant's epistemological thinking is relevant to modern science. Within the scope of library research and using a content analysis approach, by adopting the Miles and Huberman analysis model which consists of four stages, namely: data collection, data condensation, data presentation and conclusion drawing. The results of this study indicate that Immanuel Kant's epistemological thinking makes an important contribution to understanding the sources and limits of human knowledge. By introducing the concept of Copernican resolution and distinguishing between phenomena and noumena, Kant emphasized the active role of reason in understanding the phenomenal world. Concepts such as categorization, the concept of a priori, and the separation of phenomena and noumena, remain relevant in modern science. The importance of criticality, recognition of the limits of human knowledge, and awareness of subjectivity in the scientific process, also remain core principles in contemporary scientific methodology. As such, Kant's thought provides a solid foundation for understanding science today.